2018
DOI: 10.1007/s00595-018-1717-9
|View full text |Cite
|
Sign up to set email alerts
|

A single-nucleotide polymorphism in a gene modulating glucocorticoid sensitivity is associated with the decline in total lung capacity after lung transplantation

Abstract: The GLCCI1 variant was associated with a significant decrease of the TLC at 3 years after LT and the development of CLAD at 3 years, especially in patients undergoing cadaveric LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Living-donor lobar lung transplantation (LDLLT) is an established treatment for endstage lung diseases, similar to cadaveric lung transplantation (CLT) [1,2]. Long-term survival after LDLLT is comparable to that after CLT, but is hampered by the development of chronic lung allograft dysfunction (CLAD), similar to the clinical courses seen in some CLT recipients [1][2][3][4]. In bilateral LDLLT, the right and left lower lobar lungs from two different donors are implanted in place of the whole lungs of the recipient, and these unique procedural aspects may affect the characteristics of CLAD after bilateral LDLLT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living-donor lobar lung transplantation (LDLLT) is an established treatment for endstage lung diseases, similar to cadaveric lung transplantation (CLT) [1,2]. Long-term survival after LDLLT is comparable to that after CLT, but is hampered by the development of chronic lung allograft dysfunction (CLAD), similar to the clinical courses seen in some CLT recipients [1][2][3][4]. In bilateral LDLLT, the right and left lower lobar lungs from two different donors are implanted in place of the whole lungs of the recipient, and these unique procedural aspects may affect the characteristics of CLAD after bilateral LDLLT.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 4. The chronic lung allograft dysfunction (CLAD) groups after living-donor lobar lung transplantation (LDLLT) (LDLLT-CLAD) and cadaveric lung transplantation (CLT) (CLT-CLAD) had significantly lower baseline forced expiratory volume in 1 second (FEV1) values than the non-CLAD group (LDLLT-CLAD, 0.58 ± 0.053 vs. 0.92 ± 0.015, P < 0.001; CLT-CLAD, 0.51 ± 0.074 vs. 0.92 ± 0.015, P < 0.001) (A).…”
mentioning
confidence: 99%
“…In this study, the prevalence of interstitial lung disease and the preoperative use of glucocorticoids tended to be high in the low PNI group. Glucocorticoids, which are often used for interstitial lung disease and its underlying pathophysiology (such as autoimmune diseases), have been shown to reduce lymphocyte counts [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that there is a difference in lung transplant outcomes between patients with different variants of glucocorticoid-induced transcript 1 gene (GLCCI1) that modulates GC sensitivity. A study on 71 lung transplant recipients showed that compared with those with the CC variant (wild type allele), patients with the TT variant (homozygous for mutant allele) had lower total lung capacity and forced expiratory volume in 1 sec at 3 years after transplantation and also had significantly decreased chronic allograft dysfunction-free survival at year 3 after transplantation[ 19 ].…”
Section: Transplant Recipientsmentioning
confidence: 99%